Pengaruh Profitabilitas, Likuiditas Dan Leverage Terhadap Dividend Payout Ratio pada Emiten Sektor Industri Barang Konsumsi di Bursa Efek Indonesia - Kurniawan, Deden; Kristamurti, Rakhel (Fakultas Ekonomi dan Bisnis Universitas Nasional, 2021)
Purpose The purpose of this study was to determine the effect of profitability, liquidity, and leverage on the Dividend Payout Ratio (DPR). Methodology The methode of sampling in this study using purposive sampling method with the number of samples used were 16 companies from 52 manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2015-2019 with 80 observational data. The analysis technique used is multiple linear regression analysis. Findings The results of this study indicate that profitability (Return on Assets), liquidity (Current Ratio), and Leverage (Debt to Equity Ratio) have a significant positive effect on DPR in food and beverage companies listed on the IDX. 2015-2019. Suggestions Investors and potential investors who want to invest their capital should pay attention to the ROA and CR variables in a company, because these variables have a positive effect on DPR.